1992
DOI: 10.1017/s026646740000609x
|View full text |Cite
|
Sign up to set email alerts
|

The small-mammal community of a dry-tropical forest in central Thailand

Abstract: Small mammal live-trapping was carried out in a dry tropical forest mosaic in Huai Kha Khaeng Wildlife Sanctuary, central Thailand. Trapping was done in two forest types in three seasons.Maxomys surijerwas the dominant species in both plots. The three most abundant species in each plot accounted for > 90% of all captures. Community structure, density, relative abundance, biomass, age structure of populations, and habitat usage of some small mammal species varied by forest type and season. The dry evergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
5
23
2
Order By: Relevance
“…In both habitats we found some common and many rare species, a pattern that is known from other studies (e.g. Walker & Rabinowitz, 1992; Chandrasekar & Sunquist, 1996; Wu et al. , 1996).…”
Section: Species Survey and Diversitysupporting
confidence: 86%
“…In both habitats we found some common and many rare species, a pattern that is known from other studies (e.g. Walker & Rabinowitz, 1992; Chandrasekar & Sunquist, 1996; Wu et al. , 1996).…”
Section: Species Survey and Diversitysupporting
confidence: 86%
“…However, it was high compared to lower-elevation evergreen forests in southern India, such as Anamalais with three species (Chandrasekar-Rao and Sunquist 1996), Kalakkad-Mundanthurai with four species (D. Mudappa, personal communication) and Mudumalai with four species (Meena 1997). Other studies in evergreen forests in south-east Asia reported ®ve species (Wu et al 1996) and seven species (Walker and Rabinowitz 1992). Although a total of eight species were captured in this study, only four were common and two were represented by single captures.…”
Section: Community Structurecontrasting
confidence: 54%
“…That is, the annual influx of migratory antelope occurred each year between June and August, when rainfall was relatively low. Although rainfall is used as a cue to stimulate seasonal reproduction in some tropical mammals, for example rodents (Delaney and Neal, 1969;Taylor and Green, 1976;Walker and Rabinowitz, 1992;ChandrasekarRao and Sunquist, 1996), rainfall could be ruled out as a proximal cue for Crocuta since there was no apparent relationship in the current study between rainfall and either births or conceptions. The hypothesis that Crocuta time their births to minimize cub deaths from flooded dens or other mortality sources could also be ruled out because cub deaths showed no significant seasonal variation.…”
Section: Discussionmentioning
confidence: 76%